2006
DOI: 10.1111/j.1574-6968.2006.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative fatty acid profiling ofMucor rouxiiunder different stress conditions

Abstract: To understand the relationship between fatty acid metabolism and the growth morphology of Mucor rouxii, fatty acid profiling was studied comparatively in cells grown under conditions which included different atmospheric conditions or the addition of phenethyl alcohol (PEA). The significant difference in fatty acid profiles from M. rouxii grown under aerobic or anaerobic conditions was not found to be directly related to morphological growth. Oxygen limitation, which induced the formation of pure multipolar bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 31 publications
2
14
1
Order By: Relevance
“…The presence of other fatty acids such as stearic acid, lauric acid, myristic acid, pentadecanic acid, palmitolic acid, arachidic acid, ecosenoic acid, docosanoic acid, tetracosanoic acid, and tetracosaenoic acid were also detected in small amounts. The earlier studies with lipid production and fatty acid profiling of Mucorales grown either in submerged or solid-state fermentation conditions have seldom revealed the presence of fatty acids with chain length higher than C:20 [14,15,[21][22][23] as was the case in the present investigation in which fatty acids of higher chain length were also observed in trace amounts. The fatty acid profile studies from Mucorales especially Mortierella vinacea reported higher percentage values for palmitic, stearic, and linoleic [21].…”
Section: Resultscontrasting
confidence: 47%
See 1 more Smart Citation
“…The presence of other fatty acids such as stearic acid, lauric acid, myristic acid, pentadecanic acid, palmitolic acid, arachidic acid, ecosenoic acid, docosanoic acid, tetracosanoic acid, and tetracosaenoic acid were also detected in small amounts. The earlier studies with lipid production and fatty acid profiling of Mucorales grown either in submerged or solid-state fermentation conditions have seldom revealed the presence of fatty acids with chain length higher than C:20 [14,15,[21][22][23] as was the case in the present investigation in which fatty acids of higher chain length were also observed in trace amounts. The fatty acid profile studies from Mucorales especially Mortierella vinacea reported higher percentage values for palmitic, stearic, and linoleic [21].…”
Section: Resultscontrasting
confidence: 47%
“…The earlier studies for lipid accumulation and fatty acid profile during the fatty acid turnover in Cunninghamella echinulata suggested that triacylglycerols (TAGs) containing GLA were hydrolyzed with a slower rate than the other TAG molecular species [14]. Similarly, the study to observe the effect of aerobic and anaerobic conditions on the fatty acid profile of Mucor rouxii revealed that the difference in fatty acid profiles obtained under aerobic or anaerobic growth were not directly related to any particular morphology and oxygen limitation led to a decrease in long-chain fatty acids and an increase in medium-chain saturated fatty acids [15]. In agreement with the current investigation, lipid accumulation by Yarrowia lipolytica was clearly enhanced and very high quantities of lipid were accumulated in batch bioreactor experiments in which moderate aeration and agitation regimes were employed; in contrast, at high aeration and agitation rate media, insignificant lipid quantities were indeed accumulated inside the cell structures and metabolism was shifted toward the synthesis of lipid-free material [16].…”
Section: Resultsmentioning
confidence: 95%
“…It has been reported that UFAs formation in yeast and fungi were an oxygenation process, which strictly required oxygen molecules for the desaturation process and the presence of oxygen activated transcriptional expression of desaturase genes (Ruenwai et al, 2010). Significant amounts of medium-and long-chain SFAs were produced when the yeast cells were cultivated under anaerobic conditions (Jeennor et al, 2006). It is feasible to increase the total SFAs without decreasing the biomass significantly by reducing dissolved oxygen properly.…”
Section: Effect Of Dissolved Oxygen and Agitation On The Conversion Omentioning
confidence: 99%
“…Due to the fact that fatty acids and lipids are growth-associated metabolites, many researches have attempted to improve the yield of microbial oils rich in GLA (Lindberg and Hansson, 1991;Somashekar et al, 2003). In Mucor rouxii, distinguished fatty acid profiles have been found during growth development (Jeennor et al, 2006;Khunyoshyeng et al, 2002;Laoteng et al, 1999). The GLA proportion was highly accumulated in sporangiospores (Khunyoshyeng et al, 2002) and at early stages of mycelial growth in M. rouxii (Laoteng et al, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…Reduced GLA content was found in associated with an increase of oleic acid (C18:1D9) at the late logarithmic and stationary phases, which cells exposed to nutrient and oxygen limitations, in accordance with toxic substance formation. Similar to other microorganisms, variation in culture conditions, such as medium composition, temperature and gas supply, tightly influences the growth and fatty acid profiles of M. rouxii (Jeennor et al, 2006;Laoteng et al, 1999;Serrano et al, 2001).…”
Section: Introductionmentioning
confidence: 99%